Advertisement call and diel pattern of Pseudis platensis (Anura, Hylidae, Pseudinae) in the Brazilian Pantanal and a bioacoustical comparison with Pseudis paradoxa - Pérez-Granados, Cristian; Schuchmann, Karl-L.; Marques, Marinez I. (Zootaxa, 2020)
Anuran advertisement calls are life history traits associated with sexual selection and reproduction, and they play an important role in premating isolation mechanisms between species. Comparative bioacoustical analyses of these calls can be useful for taxonomic purposes. Phylogenetic relationships within the genera Pseudis are controversial, especially those related to P. platensis, which is often considered a full species or a subspecies within P. paradoxa. The advertisement call of P. platensis has not been described in detail; therefore, call comparisons of these two conspecifics have not been possible. In this study, we describe the advertisement call and diel activity pattern of P. platensis in the Brazilian Pantanal and compare the calls of P. platensis and P. paradoxa to elucidate whether acoustical parameters may help resolve the present uncertain taxonomic treatment. The advertisement call of P. platensis lasted 0.21 ± 0.01 s and consisted of a short series of 8.05 ± 0.69 distinct pulses (9.34 ± 2.94 ms of pulse duration). The vocal activity of the species was largely restricted to a few hours after dusk (7 – 11 p.m.), which is inconsistent with the diurnal and nocturnal calling behavior described for other Pseudis congeners. The advertisement calls of P. platensis and P. paradoxa were similar in note duration, number of pulses per note and dominant frequency. The geographic variation of calls within species was similar to that found among species. This bioacoustical comparison does not provide new insights into whether P. platensis should be considered a distinct species.